Investigating an optimummixing methodto produce foam concrete fulfilling the workability, density, shrinkage, strength and total volume criteria - Safawi, M.I.; Taib, S.N.L.; Hua, L.P.; Rashidi, A. (Springer, 2020)
Production of foamed concrete have the risk of encountering segregation, high shrinkage and low strength. One of the reasons for these problems is thedifficulty inmixing method. Two mixing techniques, wet and dry mixing methods, were investigated and resulting properties recorded. Five main properties characterized a foamed concrete mix and these are density, workability, shrinkage, strength and total volume. The first mixing method, wet mixing method,tend to have segregation and shrinkageproblems.The target density was difficult to achieve. Thesecondmixing method,dry mixing method,proved to achieve target density easily and lesser shrinkage problem. The dry mixing method proved to producefoamed concrete with specific target density and workability.